(3GdUMGM aj GddZIs - (3ESeGYjd Hf MeGO GdLhgQj , CHh fUQ, J (B393 (3g` s ((3GdMSjf Hf GdMSf GdGSYOi s)
(3ChdgG (B:s
(3jHJOF HHGH Gdfhf aUd GdCda s
(3BNQgG (B:s
(3jfJgi HBNQ GdcJGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B267s
Keywords: (3GddZIs